Insights into breast health issues in women's rugby - Wakefield-Scurr, J.; St. John, E.; Bibby, K.; Renwick, N.; Smith, N.; Hobbs, S.; Brown, N. (European Journal of Sport Science, 2024)
World RugbyTM supports dedicated women's welfare, injury surveillance and medical/technical interventions, yet breast health has received limited attention. This article aims to provide insights into breast health issues in rugby, including breast impacts and injuries. We discuss how breast anatomy and position may be problematic in rugby. Breast volume relates to body size, which may be increasing in women's rugby, suggesting increased breast surface area and mass, potentially increasing injury risk. Breast health issues in rugby have been reported previously, with 58% of contact footballers (including rugby) experiencing breast injuries. There are damaging effects related to these breast health issues, with breast impacts often causing pain and swelling. Breast impacts may lead to haematomas, cysts and fat necrosis which can calcify over time making them difficult to distinguish from breast carcinoma, causing further investigation and anxiety. In sport, poor bra fit and insufficient support are associated with pain, skin strain and performance decrements. This article reports the potential implications of these breast health issues on performance in rugby. Recent breast-related projects supported by rugby communities may address recommendations identified in the literature for robust breast injury classifications, updated injury surveillance systems and prospective data collection on breast injury prevalence, severity and impact in rugby. These data should inform breast injury care pathways and intervention research, including evidence-based bra design. Understanding the implications of breast impacts on tissue properties, health and wellbeing is vital. Finally, data should inform rugby-specific breast education, raising awareness of this aspect of athlete health.